Model Pelatihan Berjenjang untuk Meningkatkan Kemampuan Kader Posyandu dalam Mengukur Antropometri Anak di Kabupaten Demak, Indonesia: Tiered Training Model to Improve the Skills of Posyandu Cadres in Measuring Child Anthropometry in Demak Regency, Indonesia - Suyatno, Suyatno; Kartasurya, Martha Irene; Susanto, Henry Setyawan (Universitas Airlangga, 2024)
Background: Posyandu cadres still lack the skills to measure anthropometry. Not all cadres received regular training. Objectives: This study aims to develop a training model to improve the skills of Posyandu cadres in conducting anthropometric measurements. Methods: This study used a research and development approach with two main stages. The first stage was the development of the training model. The second stage was field testing of the new training model, using a pretest-posttest control group design. The training model in the form of Training of trainers (ToT) was tested to 49 cadres in the treatment and control groups with expert resource persons, followed by grassroots training with 142 cadres in the treatment group and 146 cadres in the control group with resource persons from the ToT participants. The intervention lasted three months. The effect of applying the training model on changes in the ability of cadres in anthropometric measurements was analyzed using the General Linear Model with a significant p-value <0.05. Results: The developed anthropometry training model is tiered training, including ToT followed by grassroots training. Through the implementation of this training model, the number of trained cadre participants increased threefold. The results of the tiered anthropometry training model trial proved to improve knowledge, attitude, practice, self-efficacy, as well as the precision and accuracy of measuring the length, height, and weight of children by Posyandu cadres (p<0.05). Conclusions: The implementation of a tiered anthropometry training model can increase cadre participants and improve the capacity of cadres in measuring child anthropometry.